Case Report: Eosinophilic gastritis with pyloric stenosis in immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome - Ronghua Yu; Yongmei Xiao; Wuhen Xu; Ting Zhang; Ting Zhang; Yizhong Wang; Yizhong Wang; Hui Hu (Frontiers in Pediatrics, 2022)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare X-linked recessive immunodeficiency caused by mutations in the forkhead box protein 3 (FOXP3) gene. IPEX is characterized by the onset of intractable diarrhea, type 1 diabetes mellitus (T1DM), and eczema in the early stages of life. The typical clinic triad for IPEX is not always seen. Here, we report a 15-year-old male patient with atypical IPEX syndrome complicated with severe eosinophilic gastritis (EG) and pyloric stenosis. The patient had noticeable eczema during the first year of life and had a history of food allergies. At the age of 3 years, the patient was diagnosed with EG, Helicobacter pylori (HP) infection, pyloric stenosis with recurrent vomiting, and failure to thrive. The patient did not respond to long-term symptomatic treatments in the following years, including methylprednisolone, proton pump inhibitors (PPI), L-glutamine and sodium gualenate granules, anti-HP therapy, and balloon dilation. At the age of 12 years, the patient received surgical interventions, including a laparoscopic jejunostomy feeding tube placement, gastrojejunal anastomosis bypass, and jejunal-jejunal end-to-side anastomosis. Intractable diarrhea and T1DM were not present in the patient. At the age of 14 years, the patient was diagnosed with IPEX syndrome due to a c.748–750del (p.Lys250del) mutation in the leucine zipper domain of the FOXP3 protein. The patient underwent matched sibling peripheral blood hematopoietic stem cell transplantation (HSCT) and showed good evolution after 3 months of HSCT. In summary, this case report provides information of unusual gastrointestinal findings in IPEX syndrome and highlights the need for increased awareness and early diagnosis of IPEX syndrome, which is vital for improving the patient's outcome.